Regulation of HuR structure and function by dihydrotanshinone-I. Issue 16 (18th July 2017) - Lal, Preet; Cerofolini, Linda; D'Agostino, Vito Giuseppe; Zucal, Chiara; Fuccio, Carmelo; Bonomo, Isabelle; Dassi, Erik; Giuntini, Stefano; Di Maio, Danilo; Vishwakarma, Vikalp; Preet, Ranjan; Williams, Sha Neisha; et al.
Abstract: The Human antigen R protein (HuR) is an RNA-binding protein that recognizes U/AU-rich elements in diverse RNAs through two RNA-recognition motifs, RRM1 and RRM2, and post-transcriptionally regulates the fate of target RNAs. The natural product dihydrotanshinone-I (DHTS) prevents the association of HuR and target RNAs in vitro and in cultured cells by interfering with the binding of HuR to RNA. Here, we report the structural determinants of the interaction between DHTS and HuR and the impact of DHTS on HuR binding to target mRNAs transcriptome-wide. NMR titration and Molecular Dynamics simulation identified the residues within RRM1 and RRM2 responsible for the interaction between DHTS and HuR. RNA Electromobility Shifts and Alpha Screen Assays showed that DHTS interacts with HuR through the same binding regions as target RNAs, stabilizing HuR in a locked conformation that hampers RNA binding competitively. HuR ribonucleoprotein immunoprecipitation followed by microarray (RIP-chip) analysis showed that DHTS treatment of HeLa cells paradoxically enriched HuR binding to mRNAs with longer 3′UTR and with higher density of U/AU-rich elements, suggesting that DHTS inhibits the association of HuR to weaker target mRNAs. In vivo, DHTS potently inhibited xenograft tumor growth in a HuR-dependent model without systemic toxicity.